Measurement report: Altitudinal variation of cloud condensation nuclei activation across the Indo-Gangetic Plain prior to monsoon onset and during peak monsoon periods: results from the SWAAMI field campaign - M. R. Manoj; S. K. Satheesh; S. K. Satheesh; S. K. Satheesh; K. K. Moorthy; J. Trembath; H. Coe (Atmospheric Chemistry and Physics, 2021)
Vertical distributions (altitude profiles) of condensation nuclei (CN) and cloud condensation nuclei (CCN) and their spatial variations across the Indo-Gangetic Plain (IGP) have been investigated based on airborne measurements carried out during the SWAAMI field campaign (June to July 2016) capturing the contrasting phases of the Indian monsoon activity in 2016 just prior to its onset and during its active phase. Prior to the monsoon onset, high concentrations of CN and CCN prevailed across the IGP, and the profiles revealed frequent occurrence of elevated layers (in the altitude range 1–3 km). Highest concentrations and elevated peaks with high values occurred over the central IGP. The scenario changed dramatically during the active phase of the monsoon, when the CN and CCN concentrations dropped (CN by 20 % to 30 % and CCN by 6 % to 25 %) throughout the IGP with more pronounced changes at altitudes higher than 3 km where decreases as high as > 80 % were observed. These reductions have an east-to-west decreasing gradient, being most remarkable in the eastern IGP and very weak over the western IGP where the CN concentrations above 3 km increased during the monsoon. The activation ratios (ARs) showed contrasting features, increasing with increase in altitude, prior to the onset of monsoon, reversing the trend to decrease with increase in altitude during the active phase of the monsoon. The supersaturation spectrum became flatter during the active phase of the monsoon, indicating an increase in the hygroscopicity of aerosols following the mixing of surface-based emissions with the advected marine air mass.